Reimagining Popular Notions of American Intellectualism : Literacy, Education, and Class - Bradbury, Kelly (Book collections on Project MUSE., 2016)
"This book calls us to rethink what it means to practice intellectualism in the twenty-first century. It surveys the evolution of contemporary limited notions of intellectualism and then reexamines the literacy and learning practices of three nonelite sites of adult public education in light of a more inclusive definition of intellectualism"--